ARUNDHATI ROY’S THE MINISTRY OF UTMOST HAPPINESS: A POSTCOLONIAL STUDY OF THE NEW SUBALTERN IN ARUNDHATI ROY’S - M. Suresh; Lakshmi (The journal of contemporary issues in business and government, 2019)
Since the Indian subcontinent gained its independence from colonial rule, postcolonial theory has consistently ranked among the most popular academic topics of study in the world. It is the result of a post-colonial condition that has resulted in a massive amount of literature being written about "subaltern" people. The concept of "subaltern," as well as the features connected with the word, have changed significantly as a result of improvements in socio- economic conditions. As a conscientious writer, Arundhati Roy has focussed her second novel, The Ministry of Utmost Happiness, on concealing modern socio-political issues that are significant to the study of "subalterns," notably in the South Asian setting, via the lens of fiction. Due to the book’s dedication to "The Unconsoled," it is essentially about everyone and everything that is occurring in fast changing India, notably regarding displaced and disadvantaged people. The transgender problem was brought up in the book by the protagonist or the major character of the storey. Other persistent issues, such as gender discrimination, caste inequality, capitalism, and a slew of other socio-political truths, were addressed on an equal footing. In addition to being an active activist, Arundhati Roy has a productive writing career, having written books on capitalism, globalisation, and democracy. As a result, The Ministry of Utmost Happiness is unquestionably and intuitively an explosion of the author’s observations of "The New Subaltern," who are the victims of social and political injustice, as expressed in the novel. The purpose of this thesis is to examine Roy’s portrayal of "The New Subaltern" in a democratic India context via the characters she creates and how she frames them in a post-colonial environment. Due to the fact that the study of subalterns is always evolving, this article makes an effort to track the evolution of subaltern studies in South Asia. Contribution/originality: Using Roy’s book, The Ministry of Utmost Happiness, to demonstrate her perspective of the new subaltern, this paper adds a new dimension to the field of ’Subaltern Studies’ in the broader field of postcolonial literary studies. Additionally, the novel’s characters, language, and the socio-political setting portrayed by the author are scrutinised in this process.